LINGKUNGAN KERJA, PENGEMBANGAN KARIR, DAN RETENSI KARYAWAN: BUKTI DARI CHEF STEAK DI SURABAYA DAN TUBAN - Anastashya Goenawan; Hilda Yunita Wono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The high turnover rate among steak chefs in Indonesia’s restaurant industry raises major challenges, including escalating training costs, operational instability, and inconsistent food quality. This study examines the influence of work environment and career development on employee retention among steak chefs. A quantitative survey method was applied to 32 respondents selected through purposive sampling in two branches of Restaurant X located in Surabaya and Tuban. Data were analyzed using multiple linear regression through JASP 18 software. The findings reveal that both the work environment (β = 0.489, p = 0.029) and career development (β = 0.686, p < 0.001) significantly and positively affect employee retention, with career development demonstrating the stronger effect. The regression model explains 74.5% of the variance in employee retention (R² = 0.745), indicating a strong predictive ability. These results contribute to the hospitality management literature by showing that structured development programs are more influential than environmental comfort in motivating skilled chefs to remain with their organization. Practically, the study provides managerial insights for restaurants to enhance retention through clear career pathways, competency-based training, and supportive working conditions.